Transmission of family values scale among Italian youth: an investigation of reliability, factorial validity and criterion validity - Esra Şahin; Troy E. Beckert; Paolo Albiero; Jesse P. Higgins (International Journal of Adolescence and Youth)
Socialization theory suggests that the family is an important sphere for intergenerational value transmission. During adolescence, a period of autonomy and identity development, secure parental attachment provides an environment in which transmission of family values can be done effectively. Intergenerational value transmission is linked to adolescent outcomes such as autonomy, family life satisfaction and parental attachment. However, there are no comprehensive measures assessing this process. This study introduces the Transmission of Values Scale (TVS), investigating its reliability, and validity. For factorial validity, we followed a sequential strategy, incorporating exploratory structural equation modelling (ESEM). Due to the multidimensional nature of TVS, we used bifactor models. Among 1,443 Italian youth, the bifactor ESEM model showed an excellent fit. Structural bifactor ESEM results indicated that the global TVS factor is strongly related to parent attachment, family life satisfaction and family leisure; and also different values explained unique variability in adolescent outcomes.